An Analysis Of Theme and Meaning in Robert Frost's The Road not Taken - Izzati Suhala; Rizki Nurhidayah Sitompul (ITScience (Information Technology and Science), 2026)
This study examines the relationship between theme and meaning in English literature. Literary works serve as a medium through which authors express ideas, emotions, values, and social realities. Among the various elements of literary analysis, theme and meaning play a significant role in helping readers understand the deeper messages embedded within a text. The purpose of this study is to identify the major themes presented in English literary works and analyze how these themes contribute to the construction of meaning. This research employs a qualitative descriptive method using a literary analysis approach. Data are collected from selected English literary texts and analyzed through close reading and thematic interpretation. The analysis focuses on identifying thematic patterns and examining how literary elements such as characterization, setting, plot, and symbolism support the development of meaning. The findings indicate that themes function as the central framework through which literary meanings are communicated. Themes such as identity, love, conflict, morality, and social issues provide insights into human experiences and cultural values. Furthermore, meaning is not fixed but emerges through the interaction between the text and the reader, allowing multiple interpretations depending on social, historical, and cultural contexts. The study demonstrates that theme and meaning are closely interconnected and contribute significantly to readers’ understanding of literary works. In conclusion, the analysis of theme and meaning enhances literary appreciation and critical interpretation. This study contributes to literary criticism by providing a deeper understanding of how thematic structures shape meaning in English literature and influence readers’ interpretations of literary texts. Keywords: English Literature, Theme, Meaning, Literary Analysis, Literary Interpretation